PAIR AND GROUP WORK AS EFFECTIVE TOOLS FOR IMPROVING SPEAKING FLUENCY IN ENGLISH LANGUAGE LEARNING (American Journal of Pedagogical and Educational Research, 2026)
This article examines the pedagogical effectiveness of pair and group work in enhancing speaking fluency in English language learning contexts. Drawing on communicative language teaching, sociocultural theory, and interactionist perspectives, the study explores how collaborative classroom interaction contributes to the development of oral fluency, communicative confidence, and discourse competence. Particular attention is given to the role of meaningful peer interaction, negotiation of meaning, and task-based communication in promoting spontaneous language production. Through qualitative and classroom-based analysis supported by relevant research, the paper argues that pair and group work function not merely as classroom techniques but as essential mechanisms for fostering communicative development. Findings indicate that structured collaborative speaking activities significantly improve learners’ fluency by increasing interactional opportunities, reducing affective barriers, and facilitating authentic language use.